Pengaruh Paket Informasi Terhadap Pengetahuan Keluarga Dengan Skizofrenia - Herna Alifiani (Universitas Faletehan, 2018)
Schizophrenia is a disease affecting the brain and causing disturbing thoughts, perceptions, emotions, movements, and behaviors. Schizophrenia causes sufferers to experience many problems not only in their lives but also their family. The lack of knowledge of family with schizophrenia can affect the pattern of inappropriate care at home. The purpose of this study was to determine the effect of information package about schizophrenia to the family knowledge with schizophrenia. This research used quasi-experimental with pre and post-test with control group design. The sample size is 60 families with schizophrenia. Measurement of knowledge was two times, there was before and after intervention by using questionnaire of knowledge. Statistical analysis uses dependent and independent sample T-test. The result shows the knowledge mean score before the intervention was 6,13 (SD=2,330) and after an intervention was 10,53 (SD=1,833). There is an effect of packet information on increasing the knowledge of family with schizophrenia (p-value <0,05). It is important for nurses to provide an information package to families to improve knowledge so a family can provide care and create the right environmental conditions for people with schizophrenia.